The Evolving Role of Sustainable Development in Shaping Political Progress: A Contemporary Islamic Perspective on Human Rights and Civil Institution - Serhan Ahmed, Sundus (Faculty of Sharia, IAIN Metro, 2025)
The article examines the role of sustainable development in advancing political development from a contemporary Islamic perspective, focusing on how the principles of human rights align with the functions of civil state institutions. The research explores how sustainable development initiatives, as outlined in the 2030 Agenda, resonate with Islamic values of justice, equity, and societal well-being. Employing a qualitative approach, this analysis draws on Islamic jurisprudential sources and international frameworks, such as the UN Sustainable Development Goals (SDGs) and the Universal Declaration of Human Rights, to highlight areas of alignment and divergence. Findings reveal that sustainable development can be a foundation for political development within a contemporary Islamic framework by supporting governance structures rooted in justice, accountability, and community welfare. Political development within an Islamic context refers to the evolution of governance structures that integrate justice ('Adl), equity (Qist), and accountability (Mas'uliyyah) as foundational principles. This aligns with the Islamic legal tradition, where governance is rooted in Sharia-based ethical and moral obligations. Governance models in Islamic societies incorporate participatory decision-making through institutions such as Shura (consultative councils) and Hisbah (public oversight mechanisms), ensuring justice and accountability in policy implementation. Moreover, the study identifies two primary viewpoints: one that views sustainable development as inherently conducive to political development and another that sees political frameworks, especially democratic participation, as essential for sustainable outcomes. This article underscores that contemporary Islamic principles can complement sustainable development efforts, reinforcing political stability, social justice, and institutional integrity within civil state structures.